The nomenclature of the Australasian dung beetle genera Mentophilus Castelnau, 1840 and Tesserodon Hope, 1837 (Coleoptera: Scarabaeidae: Scarabaeinae) - Cupello, Mario; Bouchard, Patrice; Hart, Maximillian; Barclay, Maxwell V.l. (Zootaxa, 2025)
Mentophilus Castelnau, 1840 and Tesserodon Hope, 1837 are scarabaeine genera endemic to Australia. Whereas the two species of Mentophilus are restricted to the western coast of the country, the 13 species of Tesserodon are much more widespread. The taxonomy and biogeography of these and other Australasian groups have been scrutinized over the past 50 years, but nomenclatural issues still persist. Here, we address them and conclude that: (1) the name “Mentophilus hollandiae Castelnau, 1840”, in use since 1974, is actually unavailable and the valid name for the species is Mentophilus carinatus (Reiche, 1841); (2) under Article 23.9.1 of the Code, precedence between the objective synonyms Aulacium Dejean, 1833, nomen oblitum, and Mentophilus Castelnau, 1840, nomen protectum (type species: Aulacium carinatum Reiche, 1841), is reverted, and the validity of Mentophilus is so preserved; (3) the grammatical gender of Tesserodon is masculine, not neuter as treated since the mid-20th century, and adjectival specific names in the nominative case must change their endings accordingly; (4) the name “Anisodon Hope, 1837” (nec Lartet, 1851, in Mammalia, nec Rosen, 1905, in Serpentes) is unavailable for failing to comply with Articles 11.5 and 11.6, and so does not threaten the validity of its synonym Tesserodon; (5) the correct original spelling is Tessarodon, a justified emendation established by the original author in an erratum, Tesserodon being formally an incorrect original spelling, thus invalid. To preserve stability, a Case is to be submitted to the International Commission on Zoological Nomenclature for the conservation of the incorrect spelling; in the meantime, prevailing usage is to be respected. A checklist is presented for all the species of Mentophilus and Tesserodon including information on synonymy, name-bearing types, type localities, and distribution.